Rapid resolution of fever and panniculitis after anifrolumab in a patient with systemic lupus erythematosus refractory to standard immunosuppression - Shunichiro Hanai; Yoshiaki Kobayashi; Taro Iwamoto; Daiki Nakagomi (Immunological Medicine)
Anifrolumab, a monoclonal antibody against type I interferon (IFN) receptor, has shown high efficacy against systemic lupus erythematosus (SLE) in clinical trials. Although rapid effects of anifrolumab against cutaneous manifestations of SLE have been reported, efficacy has still been considered to take a month or more, and shorter-term efficacy has not been described. A 29-year-old Japanese woman developed fever, erythema on the trunk and both upper and lower extremities, cytopenia, pericardial effusion, and acute confusional state and was diagnosed with SLE. Intravenous methylprednisolone pulse therapy followed by oral prednisolone at 50 mg/day improved her confusional state. Intravenous cyclophosphamide at 500 mg was added, and prednisolone was reduced to 40 mg/day. Fever and erythema on the upper extremities recurred shortly afterwards. Skin biopsy revealed panniculitis. After intravenously administering a single 300-mg dose of anifrolumab, fever resolved within a day, and erythema entirely disappeared within about 2 weeks. The serum IFN-α concentration decreased significantly after a single infusion of anifrolumab. Anifrolumab infusions every 4 weeks were continued, then prednisolone was tapered to 1 mg/day under anifrolumab therapy over 22 months. Anifrolumab may provide improvement on a daily basis even in patients refractory to the standard of care.